THE EFFECT OF SOCIODRAMA ON STUDENTSâ€™ ARABIC SPEAKING SKILL (AN EXPERIMENTAL STUDY AT SMA-IT AL-FATH PAYAKUMBUH) / ØªØ£Ø«ÙŠØ± Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªÙ…Ø«ÙŠÙ„ÙŠØ© Ø¹Ù„Ù‰ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… (Ø¯Ø±Ø§Ø³Ø© ØªØ¬Ø±ÙŠØ¨ÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„ÙØªØ Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ù…ØªÙƒØ§Ù…Ù„Ø© Ø¨Ø§ÙŠØ§ÙƒÙ…Ø¨ÙˆÙ‡) - Orizza Sativa Azahra; Rizka Widayanti (Lughawiyah: Journal of Arabic Education and Linguistics, 2022)
This study aims to find out the effect of sociodrama on students’ Arabic speaking skill at SMA-IT AL-Fath Payakumbuh. Experimental research of quantitative approach was used with pre-experimental design. Samples were 23 students of grade X at SMA-IT Al-Fath. Pre-test and post-test were administered to collect the data which then analyzed using t-test. Findings of the research described that t0 was 3.55 and ttable was 1.71 at significance level of 5% and df was 22. It indicates that t0 is higher than tt (3.55>1.71), H0 is rejected and Ha is accepted which means that there is a significant effect of sociodrama on students’ Arabic speaking skill. Finally, it can be concluded that sociodrama is one technique that can be used to improve students’ Arabic learning achievement, especially speaking skill.